2008
DOI: 10.1021/es8023513
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Carbamazepine by Mn(VII) and Fe(VI): Reaction Kinetics and Mechanism

Abstract: Experimental studies were conducted to examine the oxidation of carbamazepine, an anticonvulsant drug widely detected in surface waters and sewage treatment effluent, by potassium salts of permanganate (Mn(VII); KMnO4) and ferrate (Fe(VI); K2FeO4). Results show that both Mn(VII) and Fe(VI) rapidly oxidize carbamazepine by electrophilic attack at an olefinic group in the central heterocyclic ring, leading to ring-opening and a series of organic oxidation products. Reaction kinetics follow a generalized second-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
180
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(205 citation statements)
references
References 36 publications
(75 reference statements)
21
180
4
Order By: Relevance
“…2. The rate constants of the reaction decreased with increasing pH values as observed in previous studies [29,38,39]. These pH-dependent variations in k app could be attributed to the speciations of both ferrate and triclosan.…”
Section: Kinetics For the Reaction Of Fe(vi) With Triclosansupporting
confidence: 82%
See 1 more Smart Citation
“…2. The rate constants of the reaction decreased with increasing pH values as observed in previous studies [29,38,39]. These pH-dependent variations in k app could be attributed to the speciations of both ferrate and triclosan.…”
Section: Kinetics For the Reaction Of Fe(vi) With Triclosansupporting
confidence: 82%
“…Because the contribution of FeO 4 2− to the overall reactions of Fe(VI) is negligible, therefore the last two terms in Eq. (7) can be neglected [29,38,40,41]. As a result, Eq.…”
Section: Kinetics For the Reaction Of Fe(vi) With Triclosanmentioning
confidence: 99%
“…However, it has been shown that they are capable of efficiently degrading endocrine disruptors and antimicrobials, 161,162 as well as carbamazepine. 163 Furthermore, their disinfection byproducts are considered benign 164 and the products of their reduction (i.e., MnO 2 (s) and Fe(OH) 3 (s)) can be exploited as coagulants to further contribute to the removal of PPCPs and EfOM (see Hu et al 163 and references therein).…”
Section: Challenges Of Increased Reliance On Advanced Treatment Tementioning
confidence: 99%
“…Recently, a study demonstrated that Mn(VII) can effectively degrade carbamazepine (CBZ), with an electrophilic attack at the olefinic group in the central heterocyclic ring of CBZ, leading to the formation of a series of ring-opening oxidation products (Hu et al, 2008). In addition to CBZ, the degradation kinetics and mechanisms between Mn(VII) and three other widely used antibiotics were investigated, where the apparent second-order rate constants were reported to be 0.61 ± 0.02 M À1 s À1 (ciprofloxacin), 1.6 ± 0.1 M À1 s À1 (trimethoprim) and 3.6 ± 0.1 M À1 s À1 (lincomycin) at pH 7 and 25°C (Hu et al, 2010(Hu et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%